Incorporating Probabilistic Assessment of Risks and Optimization Methods into Submarine Outfall Projects - Mendonça, A. C. (2011)
Of all the sanitation infra-structures used nowadays, those encountered in the final step of the effluent treatment are of special importance mostly in countries where the coastline is extensively developed for housing, industry and other purposes, being almost inevitable that the chosen places for the final effluent disposal will be the sea and the estuaries. Reality has revealed the existence of gaps in experience, information and means to carry out this type of structures in the best possible conditions. Reported accidents with such installations, including accidents in Portugal, highlighted that their good working conditions are of mandatory importance to the environment, population’s welfare and economy. This calls for the application of a risk management approach, based on methodologies that account for randomness and uncertainty, that incorporate all the existing information and data, that account for the probability of failure of the structures and its consequences and, finally, that will grant a cost optimization of the project. The main goal of the project described in this paper is the development of a methodology and tools for application of probabilistic and optimization methods in the context of a risk management approach to the project of submarine outfalls. This represents an innovative research subject, both in Portugal and abroad. The main objective of this paper is to present the methodology and the tools to be used throughout the project. The interim objectives include the presentation of a list of risks associated with the project of outfalls, identification of the failure modes for these structures and their ascription to ultimate, serviceability or operational limit states. The methodology is established suiting the needs for applying probabilistic and optimization techniques to the project of these structures